2017
DOI: 10.1515/ngoe-2017-0019
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between the Intellectual Capital Disclosure and Cost of Debt Capital – A Case of Slovenian Private Audited Organisations

Abstract: The existing empirical research into the association between intellectual capital disclosures by organisations and the cost of debt is scarce or is based solely on the samples of the (large) listed organisations. Since agency issues between management/owners and lenders exist also in (large) private organisations whose financing is greatly dependent on loans and whose audited annual reports can be a source of additional information for external users, we performed an empirical research to find the answer to th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 68 publications
0
5
0
Order By: Relevance
“…Other scholars have examined the relationship between intellectual capital disclosure and the cost of debt, obtaining conflicting results. Indeed, Orens et al (2009) found a negative association between intangible information and the cost of debt, while Stropnik et al (2017) found a non-significant relationship, thus suggesting that the amount of intellectual capital information disclosed by companies has no effect on the cost of debt.…”
Section: Integrated Reporting and Cost Of Debtmentioning
confidence: 95%
“…Other scholars have examined the relationship between intellectual capital disclosure and the cost of debt, obtaining conflicting results. Indeed, Orens et al (2009) found a negative association between intangible information and the cost of debt, while Stropnik et al (2017) found a non-significant relationship, thus suggesting that the amount of intellectual capital information disclosed by companies has no effect on the cost of debt.…”
Section: Integrated Reporting and Cost Of Debtmentioning
confidence: 95%
“…In this regard, Orens et al (2009) have shown that there is a negative relationship between the amount of information relating to intellectual capital disclosed and the cost of debt. In contrast, Stropnik et al (2017) failed to find a significant relationship between intellectual capital disclosure and the cost of debt, conducting an analysis on a sample of Slovenian organizations.…”
Section: Literature Reviewmentioning
confidence: 98%
“…Finally, other studies have examined the relationship between intellectual capital disclosure and the cost of debt, with conflicting results. Orens et al (2009) highlights a negative relationship between information related to intangibles and the cost of debt, while Stropnik et al 's (2017) study using a sample of Slovenian firms fails to find any significant effect of intellectual capital disclosure on the cost of debt.…”
Section: Literature Reviewmentioning
confidence: 91%